Intrahepatic Hematoma and Haemobilia after Percutaneous Liver Biopsy: A Clinical Case Report - Goran Sarafiloski; Mimi Marinova; Pencho Tonchev (Journal of Biomedical & Clinical Research, 2021)
Assessing the severity of liver disease and predict the response to treatment in clinical practice requires the determination of the degree of inflammation progression and liver fibrosis. Percutaneous liver biopsy is the gold standard for grading and staging liver diseases. Complications are more common in the presence of vascular liver lesions, dilation of the bile ducts, ascites, or whether examination has been performed by less experienced physicians. Bleeding after liver biopsy is considered the most common cause of severe complications. Bleeding usually presents as a subcapsular or parenchymal hematoma, free intraperitoneal hemorrhage, hemobilia, or, rarely, hemothorax. The rarest of hemorrhagic complications is hemobilia, a term used to describe bleeding in the bile ducts. Hemobilia is usually suspected when there is a drop in hemoglobin after the procedure, pain in the upper right quadrant of the abdomen, hyperbilirubinemia, and unexplained gastrointestinal bleeding. The clinical manifestations range from chronic anemia to rapid, massive bleeding with hematemesis and/or melena.